Elements of Condom-Use Decision Making among South African Men Who Have Sex with Men. (September 2014) - Siegler, Aaron J.; Voux, Alex de; Phaswana-Mafuya, Nancy; Bekker, Linda-Gail; Sullivan, Patrick S.; Baral, Stefan D.; Winskell, Kate; Kose, Zamakayise; Wirtz, Andrea L.; Stephenson, Rob
South African men who have sex with men (MSM) are at increased risk for HIV infection, and male condoms are fundamental to HIV prevention programs. We explored condom use experiences through in-depth interviews with 34 South African MSM from Cape Town and Port Elizabeth. For data analysis, we generated a codebook and used the constant comparison method. Condom use reinforcing elements included use of alternative sexual strategies, having a high level of self-worth that was linked to protective behaviors, and use of ready-made condom negotiation scripts. Elements inhibiting condom use included perceiving substantial declines in sexual pleasure/performance, experiences of condom failure (possibly related to petroleum-based lubricant), and being in trusted relationships. Our findings suggest nuanced HIV prevention approaches such as bolstering condom negotiation skills based on successful tactics already in use. Further research is needed to address how to mitigate perceptions and experiences that condoms negatively impact sexual pleasure and performance.